2008
DOI: 10.1246/bcsj.81.754
|View full text |Cite
|
Sign up to set email alerts
|

Study on Facile Synthesis, Crystal Structure, and Solid-State Fluorescence of Dicyclohexane-Annelated Anthracene

Abstract: Dicyclohexane-annelated anthracene was synthesized by a new efficient method, which employed the Diels–Alder reaction between in situ-generated 2,3-dehydronaphthalene and dicyclohexane-fused furan. The molecule adopted antiparallel face-to-face slipped π-stacking in its crystal structure, which induced an excimer-like emission in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A mixture of stereomers was hydrogenated without separation in the presence of a catalyst with further dehydration and the formation of 1,4,5,8‐tetraalkyl anthracenes 200a‐d . The applicability of the described synthetic approach to the preparation of asymmetric cyclohexane‐fused anthracene was demonstrated by the same research group a year later (Scheme ) . The hydrogenation‐dehydration sequence for compound 203 turned out to be inapplicable due to the steric hindrance of the carbon–carbon double bond; therefore, one‐step deoxygenation with low‐valent titanium was performed with 66 % yield.…”
Section: Cycloaddition To Carbon–carbon Triple Bondmentioning
confidence: 99%
“…A mixture of stereomers was hydrogenated without separation in the presence of a catalyst with further dehydration and the formation of 1,4,5,8‐tetraalkyl anthracenes 200a‐d . The applicability of the described synthetic approach to the preparation of asymmetric cyclohexane‐fused anthracene was demonstrated by the same research group a year later (Scheme ) . The hydrogenation‐dehydration sequence for compound 203 turned out to be inapplicable due to the steric hindrance of the carbon–carbon double bond; therefore, one‐step deoxygenation with low‐valent titanium was performed with 66 % yield.…”
Section: Cycloaddition To Carbon–carbon Triple Bondmentioning
confidence: 99%
“…[22] We also investigated the fluorescence properties of several alkyl‐substituted anthracenes ( 18 – 23 ) and found that some of these derivatives exhibited high quantum yields in the solid state (Table 1). [23] However, there were few reports of the solid‐state fluorescence of acenes larger than anthracene. Therefore, we examined the fluorescence of alkyl‐substituted tetracenes in parallel with our previously mentioned examination of solid‐state color.…”
Section: Fluorescence Properties Of Alkyl‐substituted Tetracenesmentioning
confidence: 99%
“… [a] Excited at 325 nm; [b] absolute quantum yield in its powdered form, measured with an integrating sphere; [c] see Ref. [23a]; [d] see Ref. [23b].…”
Section: Fluorescence Properties Of Alkyl‐substituted Tetracenesmentioning
confidence: 99%
“…Organic materials exhibiting highly intense emissions in the solid state have recently received considerable interest because molecules with high absolute quantum yields are quite limited. [5][6][7][8][9][10][11][12][13][14] Although several approaches, such as substituent protection, [5] π-π stacking protection, [6][7][8] intramolecular chargetransfer transition, [9] aggregation-induced emission, [10,11] and modulating molecular arrangements, [12][13][14] have been reported, molecular design to control solid-state fluorescence is not fully understood. To develop new tetracenes with high emission efficiencies, we thought to introduce isoalkyl groups as branched alkyl side-chains instead of linear alkyl groups.…”
Section: Introductionmentioning
confidence: 99%